Quo Vadis: Pancasila Industrial Relations in Modern Slavery (A Case Study of the Oriental Circus Indonesia) - Puti Mayang Seruni; Lidia Febrianti; Halillah Zauza Putri Amri (IHSA Institute, 2026)
The alleged slavery case involving the Oriental Circus Indonesia reveals long-standing exploitation and human rights violations, including violence, forced labor, and the deprivation of victims' identities from childhood. Although the OCI denies the allegations, this case demonstrates that modern slavery persists and contradicts the principles of Pancasila industrial relations, which uphold human dignity. This study aims to examine the gap between legal norms and practice, while also opening up new research opportunities related to modern slavery from an industrial relations perspective in Indonesia. This research method is normative-empirical and descriptive-analytical. This study found that modern slavery in Indonesia is a growing phenomenon due to unequal relations between workers and employers and weak protection and supervision. Although Pancasila Industrial Relations emphasizes human dignity and justice in employment relations, without effective implementation, exploitative practices leading to slavery still have the potential to occur. Modern slavery in Indonesia still occurs despite being contrary to Pancasila Industrial Relations, as reflected in the Oriental Circus Indonesia case, which demonstrates the unequal relations, a la Karl Marx. Its persistence is fueled by poverty, low education, weak supervision, and the difficulty of proving, thus reflecting normative, structural, and cultural failures